THE BACKGROUND RADIATION AND EXPOSURE LEVELS AT VARIOUS SOUTH AFRICAN WEST COAST MILITARY UNITS - Bezuidenhout, Jacques (Scientia Militaria - South African Journal of Military Studies, 2014)
The West Coast of South Africa between St Helena Bay to the north and Langebaan Lagoon to the south is characterised by numerous granite protrusions. These outcrops are elements of the underlying Cape Granite Suite, which forms the bedrock of a large part of the Western Cape. Granite contains high levels of natural radionuclides, which results in high levels of natural background radiation in the surrounding area. The impacts of these high levels of radiation exposure on military personal are of concern. There are four military units located in this part of the West Coast, namely SAS Saldanha, 4 Special Forces Regiment, Langebaan Road Air Force Base and the Military Academy. Different sites in and around these military units were selected and soil samples were taken. Laboratory gamma ray measurements were done to determine the levels of natural radioactive nuclides in the soil samples. The radioactive nuclide concentrations were interpolated and then mapped with the help of geographic information systems (also known as geospatial information systems or GIS) software. An evaluation of the annual dose rate of military personnel at the units on the West Coast was made and found to range between 0,017 mSv/y and 0,163 mSv/y. These values were mapped and compared to the average global annual dose rate of 0,070 mSv/y. This article reports on an investigation of these results and the overall exposure levels of personnel from the various military units on the West Coast of South Africa.